Cancer Diagnostics in the Era of Precision Medicine - Ambrina khatoon; Talat Mirza (ziauddin University, 2024)
Advanced diagnostic pathology techniques have become increasingly necessary in the treatment of both cancer and non-neoplastic diseases, as targeted therapy has gained importance in recent years. This emphasizes the importance of developing and utilizing precise diagnostic techniques to identify potential targets for targeted therapy.